2009
DOI: 10.1200/jco.2008.16.0861
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography for Interim Response Assessment of Advanced-Stage Hodgkin's Lymphoma and Diffuse Large B-Cell Lymphoma: A Systematic Review

Abstract: For low- to intermediate-risk advanced-stage HL, FDG-PET performed after a few cycles of standard chemotherapy seems to be a reliable prognostic test to identify poor responders, warranting prospective studies to assess PET-based treatment strategies. For DLBCL, no reliable conclusions can be drawn due to heterogeneity. Interim PET remains an unproven test for routine clinical practice. Its use should be reserved for research settings where treatment regimens and imaging conditions are standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
162
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(171 citation statements)
references
References 34 publications
2
162
3
4
Order By: Relevance
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
“…Terasawa et al 3 reported a wide variation in the results of their recent meta-analysis, which is probably related to the lack of uniform and standardized criteria of interpretation. 3 In addition, data regarding the reproducibility of interim PET interpretation have been published by Horning et al, 35 who concluded that there is still moderate examination reproducibility among nuclear medicine experts, thus indicating the need to standardize PET interpretation criteria in current clinical practice. A successful attempt has been documented by Barrington et al 36 for Hodgkin disease, wherein very good agreement was achieved in the reporting of interim PET scans between expert readers from 4 different European centers using a 5-point scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to prospective studies to assess PET-based treatment strategies. 48 In contrast, due to heterogeneity in DLBCL, no reliable conclusions can be drawn, and interim PET scans remain investigational in this disease. Interim PET scans in patients with DLBCL should therefore be reserved for research studies in which treatment regimens and image interpretation are standardized.…”
Section: Interim Scans (To Direct Treatment)mentioning
confidence: 99%
“…Interim PET scans in patients with DLBCL should therefore be reserved for research studies in which treatment regimens and image interpretation are standardized. 48 Initial retrospective studies in DLBCL suggested a dramatic difference in outcome for patients with positive and negative findings on interim PET. 49,50 Subsequent prospective studies have not found such a dramatic difference, and some patients with a positive interim PET result may still have a favorable outcome.…”
Section: Interim Scans (To Direct Treatment)mentioning
confidence: 99%